The supply of affordable urban housing, squatter upgrading and land readjustment - Yusoff, Nooraini; Sutan Saidi, Noor Sharipah (Fakulti Alam Bina, UTM, 1998)
Rapid urban development has made it virtually impossible for housing especially for the low income person to be located at strategic and desirable locations within the urban areas. This is because most often than not housing has to compete with more profitable landuses for sites within the urban areas and by virtue ofits nature housingfor the "poor" would either loose out or be relegated to other less appropriate locations. It is important to realise that to a low income person where he lives is more important than the house he lives in. It is vital for him to be close to his work and most important, he has to bein the city so that hisfamily can help earn thefamily income. Hence, if the low income person is to survive economically he will need to live near the job opportunities. Nevertheless, the most prevalent fonn ofaffordable housing available to the low income person in the urban areas are in the squatter settlements. However, a typical reactionary response to these settlements has been to relocate the squatters without realising that relocation generally tends to ignore the already limited resources available for the provision of housing and more important, it illegitimatises most, ifnot all of the existing low income housing stock. The principal effect has been to reduce on an already insufficient housing stock. It fails to see the opportunities and potentials for real improvements and upgrading in the existing housing conditions of the urban poor through land readjustment. There is already in existence a system which has provided a great number of housing solutions to the urban poor, namely the squatters' housing sub-system. It is however, recognised that these settlements are not without problems. Nevertheless, considering the relative size of the population that they shelter, the dwelling units are obviously not without value either. This paper will attempt to highlight the need for squatter upgrading possibly through the application of land readjustment within the urban areas as an alternative to relocation and as a means ofensuring the supplyofaffordable housing.